Ebu’l-Vefa’nın “Fima Yahtacü İleyhi’s-Süna’ü min A’mâli-l Hendasati” kitabının geometrik tezyinata katkısı - Haddad, Makram (My University, 2015)
Bu araştırmanın amacı Süleymaniye Kütüphanesi’nde bulunan “Kitâb Fîmâ Yehtâcü İleyhi’s-Sâni‘ Min A‘mâli’l-Hendese” başlıklı eserin Ebü'l-Vefâ el-Bûzcânî'ye âidiyeti meselesini ele almaktır. Eserin kime ait olduğunu tespit edebilmek için bu araştırmada dayandığımız iki temel nüshanın tercüme ve tahkikiyle işe başladık. Bu nüshaların ilki, Ebü’l-Vefâ el-Bûzcânî’ye atfedilen Süleymaniye nüshası; diğeri ise Fârâbî’ye atfedilen Uppsala Üniversitesi Kütüphanesi’nin Torenberg koleksiyonunda kayıtlı “el-Hiyel el-Rûhâniyye ve’l-Esrâr et-Tab‘iyye fi Dakā’iki el-Eşkâl el-Hendesiyye” adlı nüshasıdır. Her ne kadar bazı araştırmacılar bu yazmanın Fârâbî’ye ait olduğu konusunda ısrarcı olsalar da biz bu makalede çeşitli delillerden yola çıkarak bu nüshanın Bûzcânî’ye ait olduğunu ortaya koymaya çalıştık. Bizzat eser üzerinde yaptığımız incelemeler bizi bu kanaate sevk etmiştir.

This research is aiming to study a rare manuscript of al-Fārābī called Kitāb al-Ḥiyal al-rūḥānīyah wa-al-asrār al-ṭabī‘īyah fī daqā’iq al-askhal al-handasīyah in order to proof that this manuscript is merely a copy of The work of Abu al-Wafa’ Muhammad ibn Muhammad al-Buzjani (940-998) with a slightly different title: Kitab fima yahtaj ilayh al-sani’ mina al-a’mal al-handasiyah (The book about what the craftsman needs of geometrical constructions). So it seems that this is a work by al-Farabi, and whatever the exact authorship we found out that it merits further study. The treatise of al-Farabi contains the foreword and 10 books (maqalat). All 10 books are included as a whole into Abu al-Wafâ’s treatise: The first book (makala) coincides with the second half of the II chapter of Abu al-Wafâ from 9 proposition to the end, the II-IX books entirely coincide with III-X chapters of Abu al-Wafâ, The X book coincides with the first half of the XI chapter of Abu al-Wafâ. So we find that it resembles the work of Abu al-Wafa’ al-Buzjani and we tryed to proof our vue with some proofs.
Keywords: Ebu’l-Vefa. Fima Yahtacü İleyhi’s-Süna’ü min A’mâli-l Hendasat; İslam; Sanat; Tarih